Reliability of technologies to measure the barbell velocity: Implications for monitoring resistance training - Martínez-Cava, A.; Hernández-Belmonte, A.; Courel-Ibanez, J.; Morán-Navarro, R.; González-Badillo, J. J.; Pallarés, J. G. (PLOS ONE, 2020)
This study investigated the inter- and intra-device agreement of four new devices marketed for barbell velocity measurement. Mean, mean propulsive and peak velocity outcomes were obtained for bench press and full squat exercises along the whole load-velocity spectrum (from light to heavy loads). Measurements were simultaneously registered by two linear velocity transducers T-Force, two linear position transducers Speed4Lifts, two smartphone video-based systems My Lift, and one 3D motion analysis system STT. Calculations included infraclass correlation coefficient (ICC), Bland-Altman Limits of Agreement (LoA), standard error of measurement (SEM), smallest detectable change (SDC) and maximum errors (MaxError). Results were reported in absolute (m/s) and relative terms (%1RM). Three velocity segments were differentiated according to the velocity-load relationships for each exercise: heavy (= 80% 1RM), medium (50% < 1RM < 80%) and light loads (= 50% 1RM). Criteria for acceptable reliability were ICC > 0.990 and SDC < 0.07 m/s (~5% 1RM). The T-Force device shown the best intra-device agreement (SDC = 0.01-0.02 m/s, LoA <0.01m/s, MaxError = 1.3-2.2%1RM). The Speed4Lifts and STT were found as highly reliable, especially against lifting velocities =1.0 m/s (Speed4Lifts, SDC = 0.01-0.05 m/s; STT, SDC = 0.02-0.04 m/s), whereas the My Lift app showed the worst results with errors well above the acceptable levels (SDC = 0.26-0.34 m/s, MaxError = 18.9-24.8%1RM). T-Force stands as the preferable option to assess barbell velocity and to identify technical errors of measurement for emerging monitoring technologies. Both the Speed4Lifts and STT are fine alternatives to T-Force for measuring velocity against high-medium loads (velocities = 1.0 m/s), while the excessive errors of the newly updated My Lift app advise against the use of this tool for velocity-based resistance training